2015
DOI: 10.1016/j.ultsonch.2015.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Sonochemical degradation of naphthol blue black in water: Effect of operating parameters

Abstract: In this work, the sonochemical degradation of naphthol blue black (NBB), an acidic diazo dye, in water was investigated. The effects of several operating parameters such as initial NBB concentration, acoustic intensity, ultrasonic frequency, nature of the dissolved gas and solution pH on the degradation of the dye were carried out. The obtained results showed that ultrasound completely destroyed NBB (5 mg L(-1)) after 45 min of sonication and most of the chemical oxygen demand was eliminated after 90 min of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 89 publications
(49 citation statements)
references
References 50 publications
6
32
1
1
Order By: Relevance
“…It can be observed from this figure that the degradation of BR29 was faster at an acidic pH and much slower at alkaline pH conditions. The difference in degradation rates between pH levels of 3.0 and 5.6 is relatively highly consistent with the findings of Ferkous et al 43 during the sonochemical degradation of naphthol blue black dye at 585 kHz. It was, however, nonsignificant between natural and alkaline pH levels.…”
Section: Effect Of Initial Phsupporting
confidence: 91%
See 1 more Smart Citation
“…It can be observed from this figure that the degradation of BR29 was faster at an acidic pH and much slower at alkaline pH conditions. The difference in degradation rates between pH levels of 3.0 and 5.6 is relatively highly consistent with the findings of Ferkous et al 43 during the sonochemical degradation of naphthol blue black dye at 585 kHz. It was, however, nonsignificant between natural and alkaline pH levels.…”
Section: Effect Of Initial Phsupporting
confidence: 91%
“…This was reported by several studies and was supported by the fact that H 2 O 2 production rates were decreased with the increase in pollutants concentrations. 41,43,44 In our case, the production rate of H 2 O 2 with respect to the initial dye concentration, which is integrated in Figure 6, supports the above explanation.…”
Section: Effect Of Initial Br29 Concentrationsupporting
confidence: 88%
“…2. As seen from this figure, sonication alone degraded efficiently NBB, which is mainly due to the • OH radical attack at the bubble/solution interface, as demonstrated early [48,49]. It should also be mentioned that previous efforts have demonstrated that the degradation rate of NBB cannot be associated with a first-order law [48].…”
Section: Sonolytic Degradation Of Nbb In the Presence Of Psmentioning
confidence: 59%
“…As can be seen from Table 3, the experimental measurements of H 2 O 2 and the estimated production rate of • OH support this statement and confirm the lower sonochemical effect of 20 kHz compared to 585 kHz. The frequency of ultrasound affects directly the single bubble yield and the number of active bubbles [48]. As the frequency of ultrasound increased from 20 to 585 kHz, the production of • OH radicals from each bubble decreased from 3.81× 10 -11 mol to 9.82× 10 -16 mol but the number of active bubbles increased drastically from 4.594× 10 2 L -1 s -1 to 1.310× 10 8 L -1 s -1 .…”
Section: Ps-enhanced Effect Dependence Of the Operating Frequencymentioning
confidence: 99%
“…To show how the difference in H 2 O 2 production rates corresponds to substrate degradation, material balances for substrate, H 2 O 2 and OH in the liquid phase have been carried out in our previous work (Ferkous et al, 2015a) and have allowed to determine a direct correlation between the production rates of H 2 O 2 in water (r H2O2 ) w and in substrate solution (r H2O2 ) s and the disappearance rate of the substrate (r s ):(r H2O2 ) s ¼ (r H2O2 ) w À 0.5r s . According to this correlation, the AO7 initial degradation rate can be predicted as r AO7 ¼ 2bðr H2O2 Þ w À ðr H2O2 Þc s , which gives a value of 2 lM/min (0.7 mg/LÁmin).…”
Section: Resultsmentioning
confidence: 99%